ATF6 deficiency damages the development of spermatogenesis in male Atf6 knockout mice. (13th December 2021) - Yu, Ru; Chen, Xihua; Zhu, Xilin; He, Bin; Lu, Cong; Liu, Ying; Xu, Xiangbo; Wu, Xiaopan
Abstract: Activating transcription factor 6 ( ATF6 ), also known as ACHM7, ATF6A, encodes a transcription factor that activates target genes for the unfolded protein response (UPR) during endoplasmic reticulum (ER) stress. It functions as nuclear transcription factor via a cis‐acting ER stress response element (ERSE) that is presented in the promoters of genes encoding ER chaperones. Studies have shown that endoplasmic reticulum stress (ERS) can cause damage to spermatozoa and testes, leading to male sterility. And we find that the expression of ATF6 in spermatozoa of some infertile patients is significantly reduced. Then, we construct the Atf6  knockout mice model and interestingly find a decline in male fertility. The downstream gene testis‐specific serine/threonine‐protein kinase 4 ( Tssk 4 ) is screened based on transcriptome sequencing. We use Western blot and real‐time PCR to confirm this result in both 293T cells and Atf6  knockout mice. TSSK4 is essential in male germ cell genesis and sperm maturation. Our results suggest that the expression of TSSK4 may be regulated by ATF6 . The effect of Atf6  knockout on the reproductive development of male mice may be related to the low expression of TSSK4, which further verify that there may be some relationship between ERS and male reproduction.